Towards a natural classification of Dothideomycetes 3: The genera Muellerites, Trematosphaeriopsis, Vizellopsis and Yoshinagella (Dothideomycetes incertae sedis) - Dai, Dong-Qin; Bahkali, Ali H.; Bhat, D. Jayarama; Xiao, Yuan-Ping; Chukeatirote, Ekachai; Zhao, Rui-Lin; Mckenzie, Eric H.c.; Xu, Jian-Chu; Hyde, Kevin D. (Phytotaxa, 2014)
We re-examine the generic types of genera with unclear placement in Dothideomycetes. These genera were hitherto poorly illustrated or described. Following examination their appropriate familial or ordinal level placements based on modern morphology concepts may be better understood. The generic types of Muellerites, Trematosphaeriopsis, Vizellopsis and Yoshinagella were re-examined in this study. Muellerites is placed in Dothidotthiaceae, Vizellopsis in Asterinaceae, while Trematosphaeriopsis and Yoshinagella are retained in Dothideomycetes incertae sedis, as they are not typical of any existing families of Dothideomycetes. By illustrating and redescribing the genera we expect renewed interest for recollection and molecular study so that these dothideomycetous genera can be placed in a natural taxonomic framework.